2012
DOI: 10.1682/jrrd.2011.03.0047
|View full text |Cite
|
Sign up to set email alerts
|

Effect of velocity on shoulder muscle recruitment patterns during wheelchair propulsion in nondisabled individuals: Pilot study

Abstract: Abstract-This study investigated how the recruitment patterns of shoulder muscles were influenced by wheelchair propulsion speed. Electromyography (EMG) activity of seven muscles was recorded with surface electrodes on 15 nondisabled subjects during wheelchair propulsion on a stationary ergometer. Kinetic data were measured by a SmartWheel. EMG total intensities were calculated to describe the muscle activation level, while the angles formed by first principal component and second principal component loading s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(46 reference statements)
0
2
0
2
Order By: Relevance
“…These results were obtained under maximal test conditions. However, Qi et al [30] have shown that velocity influences temporal and kinetic parameters. Thus, inducing variations in these parameters for higher velocity [30].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…These results were obtained under maximal test conditions. However, Qi et al [30] have shown that velocity influences temporal and kinetic parameters. Thus, inducing variations in these parameters for higher velocity [30].…”
Section: Plos Onementioning
confidence: 99%
“…However, Qi et al [30] have shown that velocity influences temporal and kinetic parameters. Thus, inducing variations in these parameters for higher velocity [30]. We can assume that our results obtained in maximal tests would be different in submaximal tests.…”
Section: Plos Onementioning
confidence: 99%
“…Possivelmente, os atletas em cadeira de rodas foram capazes de aumentar sua velocidade de movimento à medida que a tarefa se tornou mais rápida, a fim de executá-la corretamente (SANTOS et al, 2014). Este estudo corrobora as características desta amostra, visto que todos já tiveram contato com a prática esportiva (BONINGER et al, 2002;QI et al, 2012).…”
Section: Fonte -Próprio Autorunclassified
“…e Gagnon et al(2015) sincronizaramos dados eletromiográficos com a aquisição de dados cinemáticos. JáMulroy et al (2004),Qi et al (2012) eYang et al (2006), utilizaram-se de sincronização com a aquisição de dados cinéticos. Outros estudos envolvendo eletromiografia e propulsão da cadeira de rodas que não necessitaram de outra metodologia como suporte, não tiveram a necessidade de definir-se início e fim do ciclo de propulsão como no experimentode Harburn e Spaulding (1986).Considerações feitas, os resultados apresentados nas Figuras 18 à 25 fornecem informações a partir de uma análise exploratória do comportamento eletromiográfico durante o curso do gesto de propulsão.…”
unclassified